2015
DOI: 10.1016/j.jacl.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of DHA-rich fish oil on PPARγ target genes related to lipid metabolism in type 2 diabetes: A randomized, double-blind, placebo-controlled clinical trial

Abstract: DHA-rich fish oil supplementation for 8 weeks increased CD36 expression in hypertriglyceridemic subjects, which might result to higher reduction in TG level, comparing with normotriglyceridemic subjects. However, this finding should be investigated in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 52 publications
0
32
0
1
Order By: Relevance
“…We have previously shown that omega‐3 fatty acids supplementation from flaxseed oil for 12 weeks to subjects with PCOS improved gene expression of PPAR‐γ, but did not affect gene expression of GLUT‐1 . However, the gene expression of PPAR‐γ was not influenced by 2400 mg/d of fish oil supplementation containing 1450 mg DHA and 400 mg EPA among subjects with T2DM for 8 weeks . In addition, no change in gene expression of PPAR‐γ was reported in certain types of cells after exposure to EPA .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We have previously shown that omega‐3 fatty acids supplementation from flaxseed oil for 12 weeks to subjects with PCOS improved gene expression of PPAR‐γ, but did not affect gene expression of GLUT‐1 . However, the gene expression of PPAR‐γ was not influenced by 2400 mg/d of fish oil supplementation containing 1450 mg DHA and 400 mg EPA among subjects with T2DM for 8 weeks . In addition, no change in gene expression of PPAR‐γ was reported in certain types of cells after exposure to EPA .…”
Section: Discussionmentioning
confidence: 91%
“…We have previously shown that omega‐3 fatty acids supplementation from flaxseed oil at a dosage of 1000 mg/d for 12 weeks to PCOS women significantly improved gene expression of peroxisome proliferator‐activated receptor gamma (PPAR‐γ) and low‐density lipoprotein receptor (LDLR) . However, gene expression of PPAR‐γ was not affected by 2400 mg/d of fish oil supplementation containing 1450 mg DHA and 400 mg EPA for 8 weeks among subjects with T2DM …”
Section: Introductionmentioning
confidence: 99%
“…A study of supplementation with DHA-rich fish oil in an Iranian diabetic population [27] and reviews of clinical trials of supplementation with n -3 PUFAs in different diabetic populations, have not found significant positive effects on glycemic control [17,28]. However, a recent study [23] showed that n -3 PUFA supplementation with high doses for 18 months was effective in reducing glycemia and IR in patients affected by IFG or IGT and that the regression of the condition of impaired glycemia to normoglycemia seems to be helpful in delaying the development of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Derosa et al found an increase in HDL-cholesterol and a decrease in triacylglycerides after 18 months of supplementation with n -3 PUFA, in patients with impaired glucose metabolism [23]. While in subjects with type 2 diabetes supplemented with DHA-rich fish oil, Mansoori et al found a decrease in triacylglycerides independently of their initial values [27]. However, several trials of supplementation with n -3 PUFA have not found an effect on lipid profile in adults with T2DM [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The details on the study participants and methods have been described in a previous publication [29]. Only details related to this paper are presented here.…”
Section: Methodsmentioning
confidence: 99%